Leaf extract of Morinda lucida improves pancreatic beta-cell function in alloxan-induced diabetic rats. Issue 1 (2nd January 2019) - Abdulkareem, Adam Olaitan; Igunnu, Adedoyin; Ala, Adeola Adefoluke; Olatunji, Lawrence Aderemi
ABSTRACT: Chemotherapy remains the utmost treatment for Type 1 diabetes (T1D) patients. This however, predisposes the patients to a wide range of serious complications, thus, the need for alternative therapeutic agents that target pancreatic β-cell function. This study investigated the effects of aqueous leaf extract of M. lucida (MLE) on β-cell dysfunction and atherogenic dyslipidaemia in alloxan-induced T1D in rats. Twenty-five Wister rats (156- 168g) were randomly divided into normal, diabetic, diabetic + glibenclamide (5 mg/kg), diabetic + 120 mg/kg MLE and diabetic + 240 mg/kg MLE groups (n = 5/ group). Treatments were via oral route for 14 days. Our findings revealed that, 120 mg/kg MLE significantly reduced hyperglycaemia, improved insulinaemia as well as β-cell function, and attenuated weight loss in alloxan-induced diabetic rats. The extract also attenuated ( p < 0.05) atherogenic dyslipidaemia and malondialdehyde. The activities of the extract compared favourably with glibenclamide. This study suggested that, hypoglycaemic and mitigating effects of aqueous leaf extract of M. lucida on atherogenic dyslipidaemia and pancreatic β-cell dysfunction were through reduction in lipid peroxidation. The extract may therefore represent an effective source of novel drugs against TID and cardiovascular diseases. Further study is recommended, to explore the extract's mechanism of oxidative repair.